Looking for Factors Affecting Food Security in the Province of Yogyakarta Special Region (DIY) in 2019 - Suripto Suripto; Istanti Istanti (Optimum: Jurnal Ekonomi dan Pembangunan, 2021)
Food security is closely related to community welfare and poverty. The ultimate goal of food security is to improve human welfare which can be seen from the fulfillment of one's right to food. The type of data used in this study is the data from March 2019 Susenas DI Yogyakarta. The research includes measuring the degree of food security using indicators of household income and nutritional consumption. This study uses a factor analysis of the CFA (Confirmatory Factor Analysis) method. Resilience at the national level is based on resilience at the household level. For this reason, a study on household variables is the focus of the government in realizing food security. This study identifies 13 variables of household characteristics, identification using Confirmatory Factor Analysis (CFA) to classify the variables into factors/dimensions of food security. Based on the results of research, 13 household characteristics variables are divided into 4 factors, namely the Dimension of Food Availability including the level of consumption of calories/capita/day, household BPNT acceptance in quintile 2, rice prices, and expenditure groups per capita with a loading factor of 0.80 are the dominant variables. The Food Stability dimension includes the sex of the head of the household, the number of household members, and the variable of the marital status of the head of the household is the dominant variable with a factor loading of 0.96. The dimensions of access to food to get food consist of the status of the area of residence, the status of the head of the household in the formal sector, the age of the head of the household, and the dominant variable of the education of the head of the household with a loading factor of 0.64. The dimensions of food use include the number of household members experiencing health complaints as the dominant variable with a loading factor value of 0.89 and the number of household members who have been outpatient in the last month.